Efektivitas Paradiplomasi Sister City Terhadap Pariwisata Halal Nusa Tenggara Barat (POLITEA, 2022)
This research aims to analyze the effectiveness of halal tourism paradiplomacy carried out by the West Nusa Tenggara Provincial Government or sub-state actors. Tourism is one of the strategic sectors for future development. West Nusa Tenggara has attractiveness in attracting the attention of domestic and foreign tourists, on the other hand added with halal tourism since 2016 in NTB so that the tourism industry needs creativity and uniqueness. The method used in this study is a qualitative method, where the source of information that will be obtained can be seen from various information in the form of reports, archives and sources of documentation obtained through books or the internet related to the activities of the NTB local government in promoting halal tourism. The approach that will be used is the concept of paradiplomacy and effectiveness in seeing the NTB Regional Government related to the implementation of international halal tourism.